Social Enterprise in Russia: Developing Social Entrepreneurship Models in the Russian Legal and Socio-economic Context - Blagov, Yury; Aray, Yulia (Social Enterprise in Central and Eastern Europe, 2021)
This chapter identifies the social-entrepreneurship models and the main drivers and features of their development in the legal and socio-economic context of the Russian Federation. Contemporary Russian scholars began to demonstrate interest in social-entrepreneurship issues less than fifteen years ago. A rapid development of social entrepreneurship has only been observed in Russia during the last decade, but some premises of entrepreneurial approaches to social problem-solving are deeply rooted in the past. Market-economy formation in Russia after the Soviet Union’s collapse happened gradually, and old traditions of charity and mutual aid, as well as entrepreneurship development in the social sphere, were revived step by step. In fact, some pre-Soviet approaches to solving social problems started a “second life”. The state is interested in developing social entrepreneurship as an alternative tool for solving social problems. The most important feature of social entrepreneurship in the Russian Federation is the “semi-official” nature of its development.